THE RELATIONSHIP BETWEEN MOTHERS' KNOWLEDGE AND BEHAVIOR ABOUT NUTRITION-AWARENESS FAMILY (KADARZI) TOWARDS THE NUTRITIONAL STATUS OF TODDLERS IN THE WORK AREA OF OPI COMMUNITY HEALTH CENTER - Novianty , Novianty (Jurnal Inspirasi Kesehatan, 2024)
Background: The nutritional needs of children under five years old (toddlers) can be met by mothers who implement the Nutrition Awareness Family (KADARZI) program. A nutrition-aware family is a family that is able to implement balanced nutritional behavior in their daily lives, is able to understand, recognize and overcome nutritional problems that occur in each family member. Children's nutritional problems are generally the impact of an imbalance between intake and output. In children with insufficient consumption, their immune system weakens, so that children are susceptible to diseases that can reduce their appetite and cause children to be malnourished. Research Objective: To determine the Relationship between Mothers' Knowledge and Behavior About Nutrition Awareness Family (KADARZI) to Toddler Nutritional Status. Research Method: This type of research uses observational analytical research with a cross-sectional research design, namely, by measuring or observing the independent variables of Knowledge and Behavior related to the Dependent variable of Toddler Nutritional Status. The number of subjects in this study was 65 mothers who had toddlers. Results: There is a relationship between maternal knowledge about nutrition-aware families and the nutritional status of toddlers with a p-value of 0.013 <0.05 and there is a relationship between maternal behavior about nutrition-aware families and the nutritional status of toddlers with a p-value of 0.017 <0.05. Conclusion: There is a relationship between maternal knowledge and behavior about nutrition-aware families and the nutritional status of toddlers.